The Effect of Ionic Strength and pH on the Electrostatic Stabilization of NanoRDX. Issue 9 (19th May 2017) - Doukkali, Mouhcine; Patel, Rajen B.; Stepanov, Victor; Hadim, Hamid
Abstract: In this work, 1, 3, 5‐trinitroperhydro‐1, 3, 5‐triazine (RDX) with an average crystal size of 300 nm was prepared by bead milling to examine the effect of pH and ionic strength on the Zeta potential. The results showed that nanoRDX has no isoelectric point within the entire range studied ( 2 < p H < 11 ) . The maximum Zeta potential was reached under alkaline conditions of pH 11. The results indicate that the ionic strength, even at low concentrations of NaCl (0.002 mol/L), can increase the Zeta potential of the nanoRDX by 37 %. The Derjaguin‐Landau and Verwey‐Overbeek (DLVO) theory was used to evaluate the stabilization of nanoRDX at different ionic strengths. The Hamaker constant was determined to be 1.84× 10 - 20 J and the total potential energy of interaction was computed at different electrolyte concentrations. The DLVO theory predicts that 300 nm RDX particles are stable at a low salt concentration of 0.002 mol/L and unstable at 0.1 mol/L. Turbidity test was conducted for nanoRDX dispersed in a solution of pH 11 and electrolyte concentration (NaCl) of 0.002 mol/L and compared to the nanoRDX dispersed only in water. The turbidity test qualitatively confirmed the results predicted by DLVO theory and Zeta potential measurements, showing that the nanoRDX dispersion was stabilized with the addition of electrolyte in an alkaline solution. Abstract :